Modern Methods of Crisis Management in Commercial Banks - Muydinov Mukhammadsardor Abduqayum og‘li (Academia Open, 2025)
General Background: The stability of commercial banks is a cornerstone of national economic sustainability, as these institutions serve as key intermediaries in financial resource allocation. Specific Background: However, frequent exposure to global financial shocks, digital transformation challenges, and credit risk volatility demands the adoption of modern crisis management frameworks. Knowledge Gap: Despite global progress, developing economies like Uzbekistan still face constraints in integrating advanced risk management tools, digital technologies, and governance reforms effectively. Aims: This study aims to analyze and evaluate contemporary methods of crisis management in commercial banks, focusing on their applicability and efficiency within emerging markets. Results: The findings reveal that the integration of risk management systems, stress testing, digital transformation, asset diversification, improved corporate governance, and international cooperation significantly enhances financial stability and resilience. Novelty: The research provides an in-depth assessment of how innovative, technology-driven crisis management approaches can be adapted to national banking systems undergoing reform. Implications: The study concludes that strengthening regulatory frameworks, human capital, and digital infrastructure will enable commercial banks in developing economies to better anticipate crises, maintain stability, and foster sustainable growth.Highlight : Emphasizes the role of modern crisis management methods in maintaining financial stability. Highlights the use of digital technologies and early warning systems in mitigating crises. Focuses on international practices and their adaptation to developing countries’ banking sectors. Keywords : Crisis Management, Commercial Banks, Financial Stability, Risk Management, Stress Testing